Applied psycholinguistics and multilingual cognition in human creativity - Christiansen, Bryan, 1960-; Turkina, Ekaterina (IGI Global, 2018)
"This book examines how psycholinguistics, multilingualism, and language acquisition influence human creativity as it pertains to various areas of human endeavor. It also explores how psycholinguistics and multilingualism is applied in areas such as business, economics, psychology, and technology"--